The Effect of Emotional Disclosure by Writing on the Depression of Hemodialysis Patients in Iran: A Randomized Clinical Trial - Fereshteh Khaleghi (Tabriz University of Medical Sciences, 2021)
Introduction: Depression is the most common psychological problem in patients with renal failure, and it can lead to mortality in severe cases. Effective interventions are required to promote mental health in patients on hemodialysis with various types of mental disorders. The current study aimed to evaluate the effect of emotional disclosure by writing on depression of patients on hemodialysis in Iran. Methods: This clinical trial study was carried out on 140 patients undergoing hemodialysis in hemodialysis centers of Kerman. Patients were randomly assigned into two groups of intervention and control after signing the written consent forms and completing the Depression Anxiety Stress Scale (DASS 21). The intervention group was requested to write daily the deepest emotions and intrusive thoughts within 15 to 20 minutes in four consecutive days. The control group received routine care. Then, the questionnaire was recompleted two weeks later. Finally, the data were analyzed by SPSS (version 13) using independent t-test and paired t-test. Results: The mean depression score was either moderate or high. While depression scores seemed to decrease in the intervention group after the intervention, the depression scores continued to rise following the intervention in the control group. The difference in depression scores was statistically significant between the two groups before and after the intervention. Conclusion: Emotional disclosure by writing can be effective on the level of depression in patients on hemodialysis.Simus adi omnimodipsa sam fugita dolenistiae inveles est doluptat.